2022
DOI: 10.4239/wjd.v13.i9.738
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of COVID-19 vaccines in patients with diabetes as a factor for vaccine hesitancy

Abstract: Diabetes mellitus is one of the most common comorbid conditions encountered in patients with severe acute respiratory syndrome coronavirus 2 infection accompanied by significantly increased mortality, prolonged hospital stay, and requirement of invasive mechanical ventilation. This review aims to present the effectiveness and safety profile of available coronavirus disease 2019 (COVID-19) vaccines in people with diabetes as a potential cause of hesitancy for vaccination. Data from published research proves a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 90 publications
0
7
0
1
Order By: Relevance
“…On the other hand, any significant influence of cancer, receiving chemotherapy or having a comorbidity on the risk of developing adverse events after vaccination was rejected. [50,[57][58][59][60]. However, the reduced immune response to the vaccine in recipients with chronic respiratory disorder [61][62][63][64], chronic liver disease [65], hypertension [47,49], and cancer [50,66,67] were demonstrated in several studies [68,69].…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, any significant influence of cancer, receiving chemotherapy or having a comorbidity on the risk of developing adverse events after vaccination was rejected. [50,[57][58][59][60]. However, the reduced immune response to the vaccine in recipients with chronic respiratory disorder [61][62][63][64], chronic liver disease [65], hypertension [47,49], and cancer [50,66,67] were demonstrated in several studies [68,69].…”
Section: Plos Onementioning
confidence: 99%
“…[ 36 ]. Moreover, patients with diabetes may have a comp romised immune system, leading to a more complicated course of infections, including coronavirus disease 2019[ 37 ]. Some of the immune defects described in patients with diabetes are decreased cellular response in vitro , low complement factor 4, diminished cytokine response after stimulation, reduced chemotaxis, phagocytosis, and killing of polymorphonuclear cells and macrophages[ 38 ].…”
Section: T1d and The Need For Islet Transplantationmentioning
confidence: 99%
“…The experience of immunization against Ebola in various African nations has demonstrated that social and political opposition can emerge when new vaccinations are deployed during public health emergencies [ 9 ]. Therefore, effective immunization programs must disseminate adequate safety information to counter doubts and conspiracy theories [ 10 ]. Various international publications report different prevalence rates of adult vaccine administration in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%